2009
DOI: 10.1002/cbic.200900052
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Comparison of Wild‐Type and Gatekeeper Mutant Cdk2 for Chemical Genetic Studies with ATP Analogues

Abstract: Chemical genetic studies with enlarged ATP binding sites and unnatural ATP analogues have been applied to protein kinases for characterisation and substrate identification. Although this system is becoming widely used, there are limited data available about the kinetic profile of the modified system. Here we describe a detailed comparison of the wild-type cdk2 and the mutant gatekeeper kinase to assess the relative efficiencies of these kinases with ATP and unnatural ATP analogues. Our data demonstrate that mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…There are not currently enough CDK-selective agents available to comprehensively assess which of the many CDKs should be inhibited and in which combinations to block tumor growth. In this regard, the results of chemical-genetic screens (Bishop et al, 2000;Elphick et al, 2009;Enserink et al, 2009;Zimmermann et al, 2011;Horiuchi et al, 2012;Gravells et al, 2013) may be more informative than findings from knockout animals, since drug-inhibited CDKs may more closely resemble dominantnegative than null alleles because they likely still engage their cyclin partners and the rest of the CDK regulatory machinery. Additionally, future studies will be required to determine which combinations of subset-selective CDK inhibitors must be combined to overcome primary and acquired tumor resistance to these agents.…”
Section: Pan-cdk Inhibitorsmentioning
confidence: 99%
“…There are not currently enough CDK-selective agents available to comprehensively assess which of the many CDKs should be inhibited and in which combinations to block tumor growth. In this regard, the results of chemical-genetic screens (Bishop et al, 2000;Elphick et al, 2009;Enserink et al, 2009;Zimmermann et al, 2011;Horiuchi et al, 2012;Gravells et al, 2013) may be more informative than findings from knockout animals, since drug-inhibited CDKs may more closely resemble dominantnegative than null alleles because they likely still engage their cyclin partners and the rest of the CDK regulatory machinery. Additionally, future studies will be required to determine which combinations of subset-selective CDK inhibitors must be combined to overcome primary and acquired tumor resistance to these agents.…”
Section: Pan-cdk Inhibitorsmentioning
confidence: 99%
“…Accumulated experience so far indicates that AS-kinases have the same substrate specificity as their wild-type counterparts. 3,4,56 We have validated seven novel AS-ERK2 substrates biochemically and found that all seven are phosphorylated by wild-type ERK2. Despite these results, changes in enzymes specificity are still a possibility, and all substrates should be validated before beginning in-depth biological investigation into the function of a given PTM site.…”
Section: Challenges In Chemical Geneticsmentioning
confidence: 94%
“…One unit of cyclin E1/Cdk2 [27] in 5 μL was incubated for 10 mins at 30°C with either a compound or the appropriate solvent control (2 μL of 1:1 DMSO/H 2 O or kinase buffer). The enzyme activity was then assayed following addition of a substrate mix (1 μg histone H1 from Roche and 1 μCi γ-32P-ATP in kinase buffer; total reaction volume 17 μL) for 15 min at 30°C.…”
Section: Methodsmentioning
confidence: 99%
“…Sf9 cells were grown in Graces insect media (PAA) supplemented with 10% foetal bovine serum (PAA) and incubated at 27°C. Sf9 cells were infected with baculoviruses directing the expression of cyclin E1 and GST-Cdk2 [27]. Three days post-infection, the cells were harvested by centrifugation at 1,000 rpm at 4°C for 5 min.…”
Section: Methodsmentioning
confidence: 99%